Identification of Nocturnal Visitor Insects on Penda Emas Plants (Xanthostemon chrysanthus) - Bintang Saputri, Tegar; Anggraini, Dini; Pratiwi, Ayu; Permata, Mastura; Ulpatami, Niken; Wicaksono, Anggun (Jurnal Biologi Tropis, 2024)
Nocturnal insects are insects that are active at night. Nocturnal insects tend to have sharp vision, hearing and smell abilities at night. Penda Emas (Xanthostemon chrysanthus) is a flowering plant that produces nectar so that it is often attacked by various insects. Light trap is used as a nocturnal insect trap because insects are attracted to light and fragrant aromas. This research aims to identify nocturnal insects on Penda Emas plants (Xanthostemon chrysanthus) by looking at their body morphology. This research uses descriptive and qualitative methods. This method is an exploratory survey where research is carried out directly in the field. The tools used in this research were basins, lamps, insulation, raffia rope, tweezers, jars, scissors, styrofoam, needles, petri dishes, glass objects, microscopes, cameras, vials, jars, plastic and cotton. Meanwhile, the materials used are water, soap, chloroform and alcohol. The results of this research were that 10 insect species were found from 6 orders, namely the Hymenoptera order including the Tawon Kertas Dunia Lama (Ropalidia marginata), Semut Api (Solenopsis sp.), and Tawon Parasitoid (Meteorus sp.), then the Dyptera order including the Agas Jamur (Bradysia trivittata), Nyamuk (Aedes sp.), and Lalat Daging (Sarcophaga carnaria), Order Lepydoptera namely the Ngengat Hitam species (Neumichtis sp.), Order Isoptera namely the Laron species (Coptotermes sp.), Order Coleoptera namely the Kumbang Mawar Cina species (Adoretus sinicus), and the Order Trichoptera, namely the Nyamuk Mikro species (Agraylea sp.).